Eletroforetograma de proteínas de perus (Meleagris gallopavo) vacinadas conta a doença de Newcastle durante o período de postura - Brancher, Jonine Rayane Woitexen [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Brazil has the third largest worldwide production of turkeys, and is the second largest exporter of this bird. The acute phase proteins are synthesized mainly in hepatocytes, but there is also an extrahepatic production. This is promoted by inflammatory cytokines, such as interleukins IL-1, IL-6 and tumor necrosis factor alpha (TNF-α), responsible for the induction of synthesis and secretion of these protein in response to an infection or inflammation. The purpose of this study is to demonstrate how the acute phase proteins could be used as tools to monitor the effectiveness of vaccination against Newcastle disease, using the LaSota activated and inactivated strains in female egg-laying turkeys when compared with a non-vaccinated control group. Significant differences (p<0.05) were found for the concentrations of alpha-1-acid glycoprotein between the group vaccinated with the LaSota inactivated strain and the group vaccinated with LaSota activated strain at 36 weeks. Significant differences (p<0.05) were found for the concentrations of IgG heavy chain from the group vaccinated with the LaSota inactivated strain and the group vaccinated with the LaSota activated strain at 38 weeks. In the 46th week, the total protein concentrations showed significant differences (p<0.05) between the group vaccinated with the LaSota inactivated strain and the control group. On week 48 significant differences (p<0.05) were found for the concentrations of ovotransferrin, between vaccinated birds with LaSota activated strain and the group vaccinated with the LaSota inactivated strain, and serum concentrations of IgG light chain showed a significant difference (p<0.05) between the group vaccinated with the LaSota inactivated strain in the control group. Significant differences (p<0.05) were found for the concentrations of alpha-1-acid glycoprotein between the control group and the group vaccinated with LaSota inactivated ...

O Brasil possui a terceira maior produção mundial de perus, e é o segundo maior exportador desta ave. As proteínas de fase aguda são sintetizadas principalmente nos hepatócitos, porém, também há produção extra-hepática. Isto é causado por citocinas pró inflamatórias, tais como Interleucinas IL-1, IL-6 e fator de necrose tumoral alfa (TNF-α), responsáveis pela indução da síntese e secreção dessas proteínas, principalmente pelo fígado, frente uma infecção ou inflamação. O principal propósito desta investigação é demonstrar como as proteínas de fase aguda podem servir de ferramenta para monitorar a eficácia da vacinação contra a doença de Newcastle, utilizando-se as cepas LaSota ativada e inativada em perus fêmeas em fase de produção, ao se comparar com um grupo controle não vacinado. Houve diferença significativa (p<0,05) para as concentrações da alfa-1 glicoproteína ácida entre o grupo vacinado com a cepa LaSota inativada e o grupo vacinado com a cepa LaSota ativada, na 36ª semana. Houve diferença significativa (p<0,05) para as concentrações de IgG cadeia pesada entre o grupo vacinado com a cepa LaSota inativada e o grupo vacinado com a cepa LaSota ativada, na 38ª semana. Na 46ª semana, as concentrações de proteínas totais apresentaram diferença significativa (p<0,05), entre o grupo vacinado com a cepa LaSota inativada e o grupo controle. Na 48ª semana foram observadas diferenças significativas (p<0,05) para as concentrações da ovotransferrina, entre o grupo vacinado com a cepa LaSota ativada e o grupo vacinado com a cepa LaSota inativada e as concentrações séricas da IgG de cadeia leve apresentaram diferença significativa (p<0,05) entre o grupo vacinado com a cepa LaSota inativada em relação ao grupo controle. Houve diferença significativa (p<0,05) para as concentrações da alfa-1 glicoproteína ácida entre o grupo controle e o grupo vacinado com cepa LaSota inativada, na ...
Keywords: Newcastle, Doença de; Peru (Ave) - Criação; Proteinas - Sintese; Vacinação; Ave - Doenças; Turkeys